POSTPARTUM CONTRACEPTION - Suci Nurfajriah (International Research of Multidisciplinary Analysis, 2023)
The postpartum period is critical to start using contraception because it is one way to maintain maternal health and increase maternal motivation to avoid future pregnancies. The principle of contraceptive methods in the postpartum period is a contraceptive method that does not interfere with milk production. This study method is a literature review that tries to explore postpartum contraception. Sources for conducting this literature review include systematic search  studies  of computerized databases (EBSCOHOST, Pubmed, and Cochrane Collaboration) journal studies published since 201 2-20 20.  The writing of this scientific article uses vancouver bibliography writing. The results of this literature study explain the various contraceptive methods that can be used in the  postpartum period. The study results conclude that the methods that can be used in the postpartum period are Kontap, IUD, Implant, injection, minipill, simple se method(condom, MAL, coitus interruptus).